1995
DOI: 10.1161/01.cir.92.11.3255
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind Comparison of Intravenous Amiodarone and Bretylium in the Treatment of Patients With Recurrent, Hemodynamically Destabilizing Ventricular Tachycardia or Fibrillation

Abstract: Bretylium and amiodarone appear to have comparable efficacies for the treatment of highly malignant ventricular arrhythmias. Bretylium use, however, may be limited by a high incidence of hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(132 citation statements)
references
References 28 publications
3
127
0
2
Order By: Relevance
“…But Gilmour's group (13) recently reported that the drugs verapamil (at high concentrations) and diacetyl monoxime, which flatten APD restitution by different mechanisms than does bretylium, also prevented VF in the normal canine left ventricle. And, as noted earlier, bretylium has been shown to abolish VF in both normal and diseased hearts (27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 53%
“…But Gilmour's group (13) recently reported that the drugs verapamil (at high concentrations) and diacetyl monoxime, which flatten APD restitution by different mechanisms than does bretylium, also prevented VF in the normal canine left ventricle. And, as noted earlier, bretylium has been shown to abolish VF in both normal and diseased hearts (27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 53%
“…One definition of electrical storm is recurrent ventricular tachycardia or fibrillation occurring two or more times in a 24-h period, usually requiring electrical cardioversion or defibrillation. 10,11 A broader use of the term ICD storm includes those patients who receive multiple shocks inappropriately for atrial fibrillation, lead fracture, electromagnetic noise, and so forth. The incidence of true ICD storm is estimated to occur in between 10 and 30% of all ICD recipients.…”
Section: Definition and Incidence Of Icd Stormmentioning
confidence: 99%
“…60 Once again, the target amiodarone dose ratio of 8 to 1 was compressed to 1.8 to 1 as a result of open-label boluses. There was no significant difference in the primary outcome, which was median VT/VF recurrence rate over 24 hours.…”
Section: Short-term Control Of Vt/vfmentioning
confidence: 99%